2011
DOI: 10.1111/j.1537-2995.2011.03345.x
|View full text |Cite
|
Sign up to set email alerts
|

Lookback investigations of Babesia microti–seropositive blood donors: seven‐year experience in a Babesia‐endemic area

Abstract: Recipients of components from B. microti-positive donors were infected via transfusion, with index donations from parasitemic donors posing the greatest transmission risk. This report of B. microti transmission detected through LB, coupled with ongoing TTB cases, indicates that interventions are needed to reduce transmission of B. microti to US blood recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 23 publications
0
44
0
Order By: Relevance
“…This is not new, having already been reported previously in both asymptomatic blood donors as well as patients following a diagnosis of acute babesiosis 10,14,15 Moritz et al recently reported on longitudinal follow-up of 262 seroreactive and/or PCR positive blood donors (from 2010 to 2015) using an arrayed fluorescent immunoassay (AFIA) and PCR. The median time to seroreversion was 410 days (range 24–1156) and among 129 donors followed to 1 year, 104 (81%) remained seroreactive.…”
Section: Discussionmentioning
confidence: 59%
“…This is not new, having already been reported previously in both asymptomatic blood donors as well as patients following a diagnosis of acute babesiosis 10,14,15 Moritz et al recently reported on longitudinal follow-up of 262 seroreactive and/or PCR positive blood donors (from 2010 to 2015) using an arrayed fluorescent immunoassay (AFIA) and PCR. The median time to seroreversion was 410 days (range 24–1156) and among 129 donors followed to 1 year, 104 (81%) remained seroreactive.…”
Section: Discussionmentioning
confidence: 59%
“…This finding suggests that subclinical infection persists in at least some donors for months if not longer, consistent with evidence presented in prior studies. 14,29 On the other hand, culling of EIA-reactive donors has been shown to decrease their prevalence in the donor population, 36 which may conceivably leave a preponderance of donors with new, seasonal infections.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, none of these assays are 100% sensitive and specific in every phase of infection; PCR and microscopy are superior to IFA in the acute infection phase before an immune response has developed, but antibody-based assays are more likely to detect low-level infections in the late or chronic phases, when parasite loads are ex- tremely low (14,29,30,34,50). These low-level, largely asymptomatic infections are a particular concern for transfusiontransmitted babesiosis (19,20,23,24,53). In an effort to develop an improved antibody detection technique, we surveyed B. microti total antigen Western blots for reactive bands and identified an immunodominant antigen using detergent extraction and protein sequencing techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The first human infections were identified among asplenic patients in Europe (1957) and among normosplenic residents of Nantucket Island, MA, in the United States (1970) (11,16,51,55). More recently, blood transfusions from otherwise healthy donors who harbor occult infections have been recognized as an important potential risk factor in disease transmission (1,12,19,23,32,53).…”
mentioning
confidence: 99%
See 1 more Smart Citation